The relation between attachment styles and self-esteem in adolescents - Călin, Mariana Floricica; Sandu, Mihaela Luminița; Precup, Iuliana Ioana (Technium Social Sciences Journal, 2022)
Adolescence is a unique period in the life of an individual who goes through certain changes and acquires different experiences that help him on his way to adulthood. During this period, young people form their personality, behavior and have a different view of the things around them. There are also different concepts that influence their development and implicitly their maturation. In the present study the two concepts that we have chosen to analyze in this period of adolescence are self-esteem and attachment. Self-esteem that influences the opinions of young people in several aspects of their lives and attachment that is formed in the first year of life and that affects relationships and the way in which they attach themselves to people depending on the type of attachment prevailing. The motivation for choosing the subject started from the idea that a type of attachment that has a great influence in an individual’s life on how they form relationships throughout their lives can also have an influence on self-esteem that spans several aspects of an individual’s life. They have specific characteristics for each type of attachment and level of self-esteem. The purpose of the study is to see if there is a relationship between attachment type and self-esteem and if self-esteem is influenced during the teenage period by the attachment that young people hold.